TIPOLOGI PELAKSANAAN KEWAJIBAN NAFKAH LAHIR SUAMI YANG BERSTATUS NARAPIDANA PERSPEKTIF HUKUM ISLAM (Studi Analisis Interpretasi Teori Qira’ah Mubadalah) - Yulmitra Handayani (Institut Agama Islam Negeri Batusangkar, 2020)
Obligations of conjugal need by a husband, also with the issue of responsibility and the husband's condition to provided. As a prisoner makes a polemic to be provided obligation of the husband. the loss of independence and restrictions on movement cant liability, for physically and mentally. Through this research there are can be discussed; first, how to implement the obligations of a prisoner's husband's conjugal need, and how to understand of living according to Islamic law views this crucial issue. The aim to find the burden of conjugal need status the implication by a husband, which becomes constrained and then as a prisoner. This study was analyzed using a sociological-empirical approach. The results obtained from this study, there are three typologies in the implementation of livelihood obligations of husbands who are prisoners in Rutan Batusangkar; First, implemented with the business going on, and producing. The second is not implemented, the provision of income is inadequate, and the third is not carried out, the opposite is the case, the wife always spends her husband during the criminal period. The view of Islamic law in this case doesnt contradictions, although other side liability for the husband must be fulfilled. Islam seen this with two legal standing, the first is the obligation to maintain a living on the typology of implementation. Second, conjugal need obligations fall and become debt to the typology of the implementation of less and not implemented.